Study on Types of Anterior Crucial Ligament (ACL) Remnants in Patients with ACL Injuries - Gurung, Subash; Gurung, Indra Kumar; Bhattarai Chhetri, Raju (Annapurna Journal of Health Sciences, 2026)
Background: ACL injuries account for global burden of knee injury. Anatomic ACL reconstruction using grafts is widely used modality, however tissue bridging between tibia and femur is growing recently despite fact that intrasubstance ACL injuries do not heal. ACL injury patients may have thick ACL remnants with mechanoreceptors contributing to knee proprioceptive functioning and may aid in knee stability. This study aimed to find out the prevalence of types of ACL remnants in ACL injured patients. Methods: A retrospective cross sectional study was conducted in Pokhara Academy of health Science for 1 year where a total of 23 patients who had undergone arthroscopic ACL reconstruction with or without meniscus injury . Dignostic arthroscopy was done to find out ACL remnant type. Results were expressed as percentages, mean +/- standard deviation and median for variables. P-value of <0.05 was taken as statistically significant at confidence interval of 95%. Results: Majority of the participants were male (73.9%) and age group of 20-40 year was predominant with 82.6%. Type 4 ACL remnants were predominant type with 65.2% and type 3 and type 2 were equal with 17.4% each and type 1 remnant was not found. Conclusion: As ACL injuries account for major burden of knee injury, Crain type 4 ACL remnant was the most common type. ACL remnant in our study was due to delay in diagnosis and treatment of ACL injurieKeywords:ACL injuries ;ACL remnants.Study on Types of (ACL) Remnants Background: ACL injuries account for global burden of knee injury. Anatomic ACL reconstruction using grafts is widely used modality, however tissue bridging between tibia and femur is growing recently despite fact that intrasubstance ACL injuries do not heal. ACL injury patients may have thick ACL remnants with mechanoreceptors contributing to knee proprioceptive functioning and may aid in knee stability. This study aimed to find out the prevalence of types of ACL remnants in ACL injured patients.Methods: A retrospective cross sectional study was conducted in Pokhara Academy of health Science for 1 year where a total of 23 patients who had undergone arthroscopic ACL reconstruction with or without meniscus injury . Dignostic arthroscopy was done to find out ACL remnant type. Results were expressed as percentages, mean +/- standard deviation and median for variables. P-value of <0.05 was taken as statistically significant at confidence interval of 95%.Results: Majority of the participants were male (73.9%) and age group of 20-40 year was predominant with 82.6%. Type 4 ACL remnants were predominant type with 65.2% and type 3 and type 2 were equal with 17.4% each and type 1 remnant was not found.Conclusion: As ACL injuries account for major burden of knee injury, Crain type 4 ACL remnant was the most common type. ACL remnant in our study was due to delay in diagnosis and treatment of ACL injuries.